C-terminal-truncated hepatitis B virus X protein promotes hepatocarcinogenesis by activating the MAPK pathway. (October 2021) - Zhang, Chaojun; Xiao, Chanchan; Ren, Guanhua; Cai, Dongmei; Long, Long; Li, Jilin; Li, Kezhi; Tang, Yanping; Huang, Tianren; Deng, Wei
Abstract: Purpose: C-terminally truncated hepatitis B virus X (ctHBx) is frequently detected in hepatocellular carcinoma (HCC) patients with hepatitis B virus (HBV) integrated into their genomes, but the molecular mechanisms of ctHBx-related oncogenic signaling remain unclear. In this study, the effects of ctHBx on HepG2 cells were investigated by measuring ctHBx-induced changes in the cell cycle-related target proteins cell division cycle 25C (cdc25C) and p53 downstream of the mitogen-activated protein kinase (MAPK) pathway. Materials and methods: ctHBx lentiviruses were constructed and transfected into HepG2 cells. Then, we investigated HepG2 cell line function by conducting the Cell Counting Kit-8 (CCK8) assay, clone formation assay, scratch wound testing, Transwell assays and flow cytometry to examine cell cycle and apoptosis. Western blotting (WB) was performed to detect proteins related to and downstream of the extracellular signal-regulated kinase(ERK)/c-Jun N-terminal kinase(JNK)/p38 MAPK pathway, including cdc25C and p53. Results: ctHBx significantly enhanced the proliferation, migration, invasion and colony-forming capability of HepG2 cells. In addition, ctHBx activated the ERK/JNK/p38 MAPK signaling pathway to regulate cell viability by affecting the expression of cyclin-related proteins, including cdc25C and p53. Conclusion: The present study demonstrates that ctHBx promote the formation and development of HCC via regulating MAPK/cdc25C and p53 axis. ctHBx should be the driving factor of HBV-induced hepatocarcinogenesis. Highlights: We investigated the role and potential mechanism of ctHBX regulated by MAPK pathway involving in HCC development. ctHBx significantly enhanced the proliferation, migration, invasion and colony-forming capability of HepG2 cells. ctHBx may activates the ERK/JNK/p38 MAPK pathway via regulating cdc25C and p53 axis to regulate cell viability. The conclusion about the relation of ctHBX and HCC would contribute to the prevention and treatment of HBV-induced HCC.